The Seed Weight Patterns During Imbibition and Germination Morpho-physiology of Four Maize (Zea mays L.) Seed Varieties: Imbibition Pattern and Morpho-physiological of Maize (Zea mays L.) Seed Germination - Punjung Medaraji Suwarno; Evayusvita Rustam; Abdul Qadir; Suwarto; Astryani Rosyad (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Suboptimal environmental conditions cause low imbibition rate in maize plants, thus disrupting enzyme activation and food availability for the sprouts, and inhibiting the germination process. This study aims to provide a better understanding of the imbibition pattern and physiological characteristics of germination, hopefully obtaining useful information in the development of seed processing techniques and more efficient agricultural technology. The maize seeds used in this study were the seeds of four maize varieties. The imbibition pattern was obtained by weighing the seeds from 0 to 120 hours with a 6-hour time interval. The results showed that the four varieties showed a typical three-phase imbibition pattern with almost the same time. Overall, the highest seed growth and germination was found in Jantan F1 and Paramita, which have great potential for use in seed propagation, while Baruna variety showed low seed quality and needs further evaluation for improvement.